PERAN PENDIDIKAN AGAMA HINDU DALAM MEMBANGUN SDM HINDU BERKARAKTER SERTA BERAKHLAK MULIA - IG. Agung Jaya Suryawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Hinduism Education is one of the strategies that is rightly used for Hinduism as a subsystemofnationaleducationalsoexperiencingthesameimpactontheinfluenceofglobalization,theconsequenceistoteachstudentsaboutthethingsfacedintheeraofglobalizationwiththeconceptoffundamentalteachingsofHinduismHinduismeducationcurriculumasanembodimentoftheteachingsofHinduism.HinduismanswerseveryproblemfacedinordertomaintainHinducultureandreligion.Inimprovinghumanbeingsasindividualbeingswhohavethepotentialtobephysicalandnon-physical,theyarecarriedoutbyprovidingknowledge,skills,valuesandattitudes.TheformationofvaluesisthevaluesofnationalcultureaswellasreligiousvaluesinaccordancewiththeirrespectivereligionsinordertoincreasethefaithanddevotiontoGodAlmighty.Theprocessoftransformationtakesplaceinthepathofschooleducationandeducationoutsideofschool.JohnVaizeiinhisbookEducationintheModernWorld(1965)suggestedtheroleofeducationasfollows:(1)throughinstitutionstosuggesttheroleofhighereducationandresearchinstitutionstoprovidenewideasandtechniques,(2)throughschoolsandtrainingtoprepareworkersknowledgeableskill,and(3)plantingattitudes.Fromthecollaborationofallpartiesitisexpectedthatgoodhumanresourcesandcharacterandnoblecharacter.